Computed Tomography Density and β-Amyloid Deposition of Intraorbital Optic Nerve May Assist in Diagnosing Mild Cognitive Impairment and Alzheimer’s Disease: A 18F-Flutemetamol Positron Emission Tomography/Computed Tomography Study - Wu, Han; Lei, Zhe; Ou, Yinghui; Shi, Xin; Xu, Qian; Shi, Keqing; Ding, Jing; Zhao, Qianhua; Wang, Xiuzhe; Cai, Xiaolong; Liu, Xueyuan; Lou, Jingjing; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: To study whether Computed Tomography (CT) density and β-amyloid (Aβ) level of intraorbital optic nerve could assist in diagnosing mild cognitive impairment (MCI) and Alzheimer’s Disease (AD). Methods: A total of sixty subjects were recruited in our study, including nine Normal-Control (NC) subjects, twenty four MCI subjects, and twenty seven AD subjects. All subjects conducted 18F-flutemetamol amyloid Positron Emission Tomography/Computed Tomography (PET/CT) imaging. Blinded to clinical information of the subjects, two physicians independently measured and calculated the standard uptake value ratio (SUVR) of bilateral occipital lobe, SUVR of bilateral intraorbital optic nerve, and CT density of bilateral intraorbital optic nerve by using GE AW 4.5 Workstation. Results: Between AD and NC groups, the differences of bilateral intraorbital optic nerve SUVR were statistically significant, between AD and MCI groups, the differences of left intraorbital optic nerve SUVR were statistically significant. Between any two of the three groups, the differences of bilateral intraorbital optic nerve density were statistically significant. Bilateral occipital SUVR (y) were positively correlated with bilateral intraorbital optic nerve SUVR (x), the regression equation are y = 0.5768*x + 0.9211 (Left) and y = 0.6056*x + 0.9264 (Right) respectively. Bilateral occipital SUVR (y) were negatively correlated with bilateral intraorbital optic nerve density (x), the regression equation are y = -0.0092*x + 1.486 (Left) and y = -0.0078*x + 1.501 (Right) respectively. Area under the receiver operating characteristic (ROC) curve of multiple logistic regression were 0.9167 (MCI vs. NC) and 0.8951 (AD vs. MCI). Between MCI and NC subjects, totally 81.82% subjects were correctly classified, including 66.67% NC subjects and 87.50% MCI subjects. Between AD and MCI subjects, totally 80.39% subjects were correctly classified, including 81.48% AD subjects and 79.17% MCI subjects. Conclusion: The CT density and β-amyloid SUVR of optic nerve were associated with β-amyloid SUVR of occipital cortex. The combination of intraorbital optic nerve CT density and intraorbital optic nerve SUVR could assist in diagnosing MCI and AD.